Targeting the secretory program of 3q-amplified lung cancers - Luis Pardo; Jim C. Norman (The Journal of Clinical Investigation, 2024)
Designing strategies to target cell proliferation has been a priority of cancer researchers for decades. However, targeting the secretory programs of transformed cells can influence other cancer features such as cell survival, migration, and communication with the tumor stroma. In this issue of the JCI, Tan and colleagues describe functional cooperativity between the Golgi-resident proteins Golgi integral membrane protein 4 (GOLIM4) and ATPase secretory pathway Ca2+ transporting 1 (ATP2C1) in the coordination of a secretory program in 3q-amplified cancers. Targeting these tumors with manganese (Mn2+) promoted GOLIM4 degradation and imposed a secretory blockade that impaired tumor progression and stromal cell recruitment in mice. These findings highlight the secretory program as a therapeutic target in 3q-amplified malignancies and provide a promising strategy to treat tumor progression.